2015
DOI: 10.1002/zoo.21226
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of visitor number on Kangaroos housed in free-range exhibits

Abstract: Free range exhibits are becoming increasingly popular in zoos as a means to enhance interaction between visitors and animals. However very little research exists on the impacts of visitors on animal behaviour and stress in free range exhibits. We investigated the effects of visitor number on the behaviour and stress physiology of Kangaroo Island (KI) Kangaroos, Macropus fuliginosus fuliginosus, and Red Kangaroos, Macropus rufus, housed in two free range exhibits in Australian zoos. Behavioural observations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 52 publications
(69 reference statements)
2
48
3
Order By: Relevance
“…Like Choo et al (), we investigated several different aspects of visitors including number, behavior, and the presence of a baby stroller. Visitor number had a limited influence on lemur behavior, which is similar to what other studies on free‐ranging species report (Choo, Todd, & Li, ; Sherwen et al, ). As visitor number increased locomotion and “on the ground” increased, this is supportive of the visitor attraction hypothesis (Hosey, ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Like Choo et al (), we investigated several different aspects of visitors including number, behavior, and the presence of a baby stroller. Visitor number had a limited influence on lemur behavior, which is similar to what other studies on free‐ranging species report (Choo, Todd, & Li, ; Sherwen et al, ). As visitor number increased locomotion and “on the ground” increased, this is supportive of the visitor attraction hypothesis (Hosey, ).…”
Section: Discussionsupporting
confidence: 87%
“…A recurring finding from visitor effect studies, which extends to various taxonomic groups, is that the ability to retreat from visitors lessens visitor induced stress (Carlstead & Shepherdson, ; Collins & Marples, ; Hosey, ). Thus, exhibit design is of significant importance when considering visitor effects (Sherwen, Hemsworth, Butler, Fanson, & Magrath, ). One area that visitor effect studies have almost entirely overlooked is that of free‐ranging zoo animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the aforementioned interaction between adults and squirrels (which is largely static) might have meant that squirrels were less likely to move when adults were in the enclosure. The effects of visitors on locomotion has been seen previously in captive kangaroos whom have displayed increased locomotion as visitor numbers increase (Sherwen et al, ). While Sherwen's study did not distinguish between adult and child visitors on locomotion, the different—sometimes opposing—effects of adults and children on locomotion (and other behaviors) highlighted in our study clearly demonstrates the need for this distinction to be made in future studies of the visitor effect.…”
Section: Discussionmentioning
confidence: 68%
“…For example, in one of the few studies on walk‐through enclosures, Larsen, Sherwen, and Rault () found that koalas (Phascolarctos cinereus) responded to large numbers of visitors and high noise levels by increasing vigilance behavior. Similarly, Sherwen et al () found that visitor‐directed vigilance increased with visitor number in Western grey kangaroos ( Macropus fuliginosus fuliginosus ) and red kangaroos ( Macropus rufus ) housed in walk‐through enclosures. Changes such as these, especially when they involve non‐natural behavior, can not only be detrimental to welfare per se (Montaudouin & Le Pape, ) but potentially also to visitor numbers and income as the appearance of poor welfare can negatively affect public support (Miller, ).…”
Section: Introductionmentioning
confidence: 92%